2017
DOI: 10.1177/1099800417715115
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Physical Activity and Cognitive Change in Older Latinos

Abstract: Cognitive impairment in older Latinos is a concerning issue due to the rapid growth of this population and their increased risk for dementia due to chronic disease. Evidence, primarily from studies of non-Latino Whites, suggests that physical activity (PA) may reduce cognitive decline. Few longitudinal studies have included older Latinos, objective measures of PA, or neurocognitive tests that assess domains of cognition. The purpose of this longitudinal study was to explore the relation between changes in PA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Our findings showed that those who had less decline from baseline to follow-up in self-reported light physical activity maintained episodic memory, OR = 1.16 (95% CI 1.03 – 1.32), while those who had less decline in accelerometer moderate-vigorous bouts maintained semantic memory, OR = 16.08 (95% CI 1.53 – 168.89), controlling for baseline age, chronic health problems, depressive symptoms, and acculturation. These findings suggest that maintenance of physical activity with aging may prevent cognitive decline (Halloway, Wilbur, Schoeny, & Barne, 2017).…”
Section: What Questions Did the Dissertation Answer?mentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings showed that those who had less decline from baseline to follow-up in self-reported light physical activity maintained episodic memory, OR = 1.16 (95% CI 1.03 – 1.32), while those who had less decline in accelerometer moderate-vigorous bouts maintained semantic memory, OR = 16.08 (95% CI 1.53 – 168.89), controlling for baseline age, chronic health problems, depressive symptoms, and acculturation. These findings suggest that maintenance of physical activity with aging may prevent cognitive decline (Halloway, Wilbur, Schoeny, & Barne, 2017).…”
Section: What Questions Did the Dissertation Answer?mentioning
confidence: 94%
“…I presented findings from my dissertation study at the Gerontological Society of America in 2016, and the MNRS annual conference in 2017. My dissertation findings were published in the Journal of Aging and Physical Activity (Halloway, Wilbur, Schoeny, Semanik, & Marquez, 2015) and in Biological Research for Nursing (Halloway et al, 2017).…”
Section: What Questions Did the Dissertation Answer?mentioning
confidence: 99%
“…The questionnaire also estimates caloric expenditure per week in PA, providing scores for light, moderate, and moderate-to-vigorous PA. For purposes of the present study, we are interested in leisure-time PA (moderate, moderate-to-vigorous, and total) and total PA (i.e., summation of the four lifestyle domains). The Spanish version of CHAMPS has been translated and validated with strong internal consistency (Cronbach's alpha = .76) (Rosario et al, 2008) and employed with older Latino adults (Bustamante et al, 2013;Halloway et al, 2017;Marquez et al, 2011;Stewart et al, 2006;Torres-Castro et al, 2018).…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Similar to the cross-sectional studies, no trends existed between sample size, measured activity levels and cognitive outcomes. Two studies collected PA data at multiple time points, with collection periods ranging from a monthly basis for four months (Kojima & Nagano, 2019) to a five year follow-up period (Halloway et al, 2017). Given the extremely small number of included longitudinal studies, each with their own methodological limitations and differences in study design, it is difficult to draw any meaningful conclusions or identify trends.…”
Section: Longitudinal Studiesmentioning
confidence: 99%